The Secret of Improvisation: A Duoethnographic Journey of Improvisation in Music and Dance - Snustad, Rolf Martin; Martin, Rosemary Kate (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Improvisation can be perceived as a great secret of life itself, an unattainable artistic practice, or perhaps just as an easy way out when something goes wrong. But is there more? And how can improvisation also be a way in, for the artist, for the researcher, and a disposition for living? This article unfolds as a duoethnographic journey of improvisation in music and dance. In the dialogues between two researcher-artists—one coming from the subject of music and the other from dance—discussions arise about another that inspire the other's history and lifts what their stories affect in art education, education, and research in general. In the article, we investigate how different framings of improvisational encounters might make space where space is not always obvious. We touch on different ways of understanding improvisation and how improvisation can connect with life in a broader sense, holding on to Fischlin et al's statement that “improvisation matters” (243). Could it be that improvisation is something "more" than what we now give it credit for? Are we longing for an improvisation pedagogy for life itself? Through such questions, we offer thoughts on how pedagogy and life are entangled, and how longing for more improvisation might lead us in and out of teaching, artistic co-creation, and situations in life to provide space for inclusion.